Migrant Women Victims of Intimate Partner Violence and the Criminal Justice System in Portugal - Ferreira, Joana (Journal of interpersonal violence, 2021)
Research on intimate partner violence among migrants and their experiences with the criminal justice system in Portugal is not extensive. This article presents the findings of a qualitative study conducted among seven migrant women who had been victims of intimate partner violence (IPV) in Portugal and eleven professionals from different services working with these violent situations. The data were collected through semistructured interviews with these participants, in five districts across the country. Its main aim was to explore migrant women victims of IPV experiences and perceptions of the criminal justice system in Portugal, drawing from an intersectionality approach, as well as the views of professionals intervening and providing support to this population. Research findings show that women’s perceptions and expectations are affected by previous experiences in their home countries. A comparative exercise was constantly conducted between both contexts, affecting their decision to approach the criminal justice system and shaping their perceptions of the effectiveness of its intervention. The role of children in the decision to leave the relationship was central, particularly when in interaction with the unawareness of Portuguese law. This research holds potential for a significant impact on policy making and good practice with female migrant victims of IPV. For instance, it can successfully guide policy making in the field, by addressing the gaps in knowledge regarding IPV victims and their intersecting vulnerabilities, to ensure the criminal justice system and the community are prepared to consciously respond to this phenomenon and its impact.